CMOS wireless stress sensor IC with 256‐cell sensing array for ultra‐thin applications. Issue 20 (9th September 2016) - Jiang, Hanjun; Wang, Zheyao; Yang, Shujie; Liu, Heng; Wang, Zhihua
Abstract : A wireless stress sensor integrated circuit (IC) has been implemented in 0.18 μm CMOS technology. The IC is composed of a 256‐cell stress sensing array, the current‐based sensor readout circuit, a 12 bit successive approximation (SAR) ADC and a 432 MHz wireless transmitter. The stress sensor employs orthogonally placed current source pair to measure the normal and shear stresses. The chip is backlapped to 35 μm for ultra‐thin applications such as human skin stress distribution measurement. The measured sensing nonlinearity is below 0.7%. Experiments show that the implemented IC can be used to detect the facial expression changes.